Uji In Vitro Ekstrak Akar Tuba (Derris elliptica L.) Terhadap Viabilitas Tetas Telur Ikan Mas (Cyprinus carpio L.) - RAMADHAN SUMARMIN (Prosiding Seminar Biologi, 2016)
Poison Vine used as poisonous substances to clean up the ponds from pestfishes or to help the farmers to harvest the fish. Poison Vine is Climbing Leguminosae that have rotenone as bioactive. Rotenone have couple days halflife and it coul impact to the water quality including the fish. Based on this condition, the research aimed to describe the influence of Poison Vine (Derris elliptica L.) Extract to Viability of Carpfish Egg Hatchibility (Cyprinus carpio L.). The research held in Zoology Laboratory, Biology Department of Faculty of Math and Science, Universitas Negeri Padang. The research used Completely Randomized Design with 5 treatments and 6 replication. The treatments are 0% (control /P1); 0.002% (P2); 0.003% (P3); 0.004% (P4) and 0.005%(P5). The data of hatced eggs collected after 4 days incubation. Egg hatchibility and  abnormal larvae data analized with ANOVA at p≤ 0,05 and continued by LSD test. The result showed that the avarage of egg viability at P1 92.50%;  P2 80.83%;  P3 77.50%;  P4 74.17%; and P5 72.50%. The highest hatchibility at P1 Significantly higher (p<0,05) comparison to P2, P3, P4 and P5. The avarage of normal larvae at P1 99.12%; P2 98.49%; P3 97.92%; P4 96.22%; and  P5 95.30% were not significantly (p<0,05) and so to the abnormal larvae P1 0.88%; P2 1.51%; P3 2.08%; P4 3.78%; and P5 4.71%. It can conclude that Poison Vine extract decreased the viability and hatchability of Carpfish Eggs. Keyword: Poison Vine, Viability, Hatchability, Egg Carpfish